Analysis of the Influence of Leadership and Organizational Commitment through Job Satisfaction on Performance - KR, M. Yusuf Alfian Rendra Anggoro (East Asian Journal of Multidisciplinary Research, 2024)
The aim of this research is to empirically test and analyze the influence of each variable relationship, both directly and indirectly. The first relationship is the influence of leadership and organizational commitment on job satisfaction, the second is the influence of leadership and organizational commitment on performance, and the third indirect relationship is the influence of leadership and organizational commitment through job satisfaction on performance. This research design uses a survey method with cross-section data collection through questionnaires. The sample was determined using simple random sampling with a total of 165 employees at PT. Indonesian Ship Industry (Persero) Makassar. The data analysis method used in hypothesis testing is Structural Equation Modeling (SEM) with SPSS. The research results provide evidence that leadership has a positive and significant effect on job satisfaction, organizational commitment has a positive and not significant effect on job satisfaction, leadership has a positive and significant effect on performance, organizational commitment has a positive and not significant effect on performance, job satisfaction has a positive and significant effect on performance, leadership has a positive and significant effect on performance through job satisfaction, organizational commitment has a positive and insignificant effect on performance through job satisfaction.